Subunit dissociation of certain abnormal human hemoglobins - Bunn, H. Franklin (1969)
The extent of dissociation of various hemoglobins into subunits was estimated from their elution volumes (V(e)) on G-100 Sephadex. Under the same controlled conditions carboxyhemoglobins A, A3 (A(1)), F, S, and C all had the same elution volumes. The carboxy and cyanmet derivatives of hemoglobin Kansas (a variant with very low oxygen affinity) had a relatively high V(e), indicating a decreased mean molecular weight and therefore an increased tendency to form dimers and even monomers. Conversely, the liganded derivatives of hemoglobin Chesapeake (a variant with high oxygen affinity) had a relatively low V(e), suggestive of an impaired degree of subunit dissociation. Deoxyhemoglobin Chesapeake had a V(e) identical with that of deoxyhemoglobin A. Cat hemoglobin, known to have an unusually low oxygen affinity, was found to have a higher V(e) than human, dog, rabbit, rat, or guinea pig hemoglobins. Haptoglobin is thought to bind αβ dimers in preference to the α(2)β(2)-tetramer. The comparative haptoglobin affinities of the human hemoglobins were measured by competition between the test hemoglobin and radioactive reference hemoglobin for haptoglobin binding sites. Hemoglobins A, F, S, and C all seemed to bind equally readily, but hemoglobin Kansas and cat hemoglobin showed a higher affinity, and hemoglobin Chesapeake a lower affinity. These results are in accord with recently proposed models which predict that hemoglobins which have an increased degree of subunit dissociation will have a low oxygen affinity, and vice versa.